Real‐Time FE Simulation for Large‐Scale Problems Using Precondition‐Based Contact Resolution and Isolated DOFs Constraints - Zeng, Z.; Cotin, S.; Courtecuisse, H. (Computer graphics forum, 2022)
This paper presents a fast method to compute large‐scale problems in real‐time finite element simulations in the presence of contact and friction. The approach uses a precondition‐based contact resolution that performs a Cholesky decomposition at low frequency. On exploiting the sparsity in assembled matrices, we propose a reduced and parallel computation scheme to address the expensive computation of the Schur‐complement arisen by detailed mesh and accurate contact response. An efficient GPU‐based solver is developed to parallelise the computation, making it possible to provide real‐time simulations in the presence of coupled constraints for contact and friction response. In addition, the pre‐conditioner is updated at low frequency, implying reuse of the factorised system. To benefit a further speedup, we propose a strategy to share the resolution information between consecutive time steps. We evaluate the performance of our method in different contact applications and compare it with typical approaches on CPU and GPU. This paper presents a fast method to compute large‐scale problems in real‐time finite element simulations in the presence of contact and friction.